Juvenile Localized Scleroderma. Questions of Treatment - Rinat K. Raupov; Mikhail M. Kostik (Вопросы современной педиатрии)
Juvenile localized scleroderma (JLS) is a group of childhood diseases with the main symptom — skin and subcutaneous structures lesions, without any organ involvement. There is active (inflammatory) and fibrotic phase in development of JLS. The JLS treatment during active phase (when skin lesions are reversible) is the most effective. The management is determined by the area and depth of skin lesions, appearance and spread of new lesions, presence of extracutaneous signs of the disease. Topical and systemic immunosuppressants are the basic therapy for JLS. The use of antibiotics is not suggested. Clinical scores (LoSCAT), ultrasound, thermography and magnetic resonance imaging are recommended to estimate the treatment efficacy.